Cover Art - Venkatarnatnam, Puvi (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Puvi Venkataratnam, Undergraduate student, Fall 2024 Neuropsychiatric Patient (NSCI 1000) student, College of Medicine and Life Sciences, 3000 Arlington Avenue, The University of Toledo, Toledo OH 43615.